Kontrak Sosial Robek: Analisis Sosiologi Hukum Saat Negara Gagal Berdialog, Demonstrasi Jalanan Agustus 2025 Menjadi Mahkamah Terakhir - Selvira Paulina Ananda; Indra Jaya; Indryani, Indryani; Ari Tridianto; Anak Agung Dewi Intan Parwati; Mardiman Sane; Robert L Simanungkalit (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This study examines the massive demonstrations on August 25-29, 2025, as a manifestation of the disintegration of the social contract between the people and the state. These actions stemmed from deep disappointment with the House of Representatives (DPR), sparked by the issue of allowance increases and the arrogance of council members. Using a socio-legal approach, this study argues that the demonstrations signaled a breakdown in the political and moral legitimacy of the people's representatives, where the law was no longer obeyed out of conviction, but rather out of coercion. Key findings indicate that the DPR's non-participatory legislative function, exacerbated by systemic abuse of power to serve oligarchic interests, has significantly eroded public trust. Although the quantity of DPR legislation in the 2019-2024 period increased, its quality is questionable due to the practice of "fast-track" legislation and the low completion of the National Legislation Program (Prolegnas) targets. Comparative analysis reveals a recurring pattern of protests against flawed legislation. However, the 2025 demonstrations saw a new escalation after a tragic incident that killed a protester, shifting the focus of public anger from policy issues to alleged human rights violations by the authorities. This study concludes that the restoration of trust can only be achieved through a more participatory and transparent reconstruction of the social contract, as well as firm law enforcement against individuals who betray the public mandate.